Comparative Study of the Transformation of Legal Methods in Implementing Online Marriages Between Indonesia and Singapore from a Positive Legal Perspective - Maskanah, Ummi (Faculty of Law, Universitas Pekalongan, 2024)
This research explores the use of information technology in carrying out marriage contracts, especially via video teleconference, which has become commonplace during the COVID-19 pandemic. An example of an online wedding includes a couple from Singapore who were permitted by the Registry of Marriages (ROM) to have a virtual ceremony. In the context of Islamic law, a marriage contract via teleconference shows the flexibility of sharia in facing changing times, with the concept of mashlahah (benefit) which allows reform and reinterpretation to achieve benefits. In Indonesia, although the Marriage Law does not explicitly regulate marriage via telecommunications, the decision of the South Jakarta Religious Court No. 1751/P/1989 became jurisprudence that recognized the validity of online marriages as long as the identities of the parties involved could be ascertained. Article 14 of the Compilation of Islamic Law (KHI) requires the presence of the bride and groom, guardians, witnesses, and the marriage contract in one assembly, which in teleconference conditions can be fulfilled with real-time images and sound. In Singapore, virtual marriages are officially regulated by law which allows marriage ceremonies to be conducted online with witnesses and guardians present virtually. A comparison between the two countries shows that although the technical procedures are similar, Singapore has clearer and more structured regulations compared to Indonesia. This research highlights the importance of legal flexibility and adaptation to social dynamics, ensuring that legal processes remain relevant to current developments.